Adherencia terapéutica de VIH en la población del HGZ/MF N°12 - Rueda Maldonado, Nancy (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
Introduction. Human immunodeficiency virus (HIV) is a lentivirus of the Retroviridae family, which has a prolonged incubation period. There are two types of HIV, called HIV-1 and HIV-2. In the absence of antiretroviral treatment, the evolution of HIV infection is as follows: in the acute HIV infection phase, virus replication occurs with an increase in viral load and an abrupt decrease in the CD4+ T-lymphocyte count, which is an essential part of the immune system in humans. In response to infection, a response is triggered that is capable of maintaining the infection in a prolonged asymptomatic phase, which normally lasts several years and culminates in the presence of an increase in viremia with a consequent decrease in the CD4+ T lymphocyte count, which confers immunosuppression. When the CD4+ T-lymphocyte count falls below 200 cells/mm3, or opportunistic or defining diseases appear, the person is defined as having advanced HIV disease. Objective: To determine the percentage of therapeutic adherence in HIV patients at HGZ/MF N°12. Material and Methods: on ethics and health research, a descriptive, prospective, cross-sectional, observational, quantitative study was carried out in HIV patients at HGZ/MF N°12 with the collection of information through the modified Morisky-Green collection instrument, which made it possible to determine the percentage of adherence to treatment. Descriptive statistics, association of variables using Chi-square was used. SIRELCIS registry R-2022-1603-004. Results: A total of 50 patients of both sexes were studied, 14 (28%) were women and 36 (72%) men, the average age in years was 41-60 years, 46 patients (82%) had an adequate therapeutic adherence. Conclusion: 92% of patients diagnosed with HIV at HGZ/MF No. 12 have adequate adherence to treatment.

Introducción. El virus de la inmunodeficiencia humana (VIH) es un lentivirus de la familia Retroviridae, que tiene un periodo de incubación prolongado. Existen dos tipos del VIH, llamados VIH-1 y VIH-2. En ausencia de tratamiento antirretroviral, la evolución de la infección por VIH es la siguiente: en la fase de infección aguda por VIH ocurre replicación del virus con incremento en la carga viral y un descenso abrupto de la cuenta de linfocitos T CD4+; que constituyen una parte esencial del sistema inmunológico en los seres humanos. Como respuesta a la infección, se desencadena una respuesta que es capaz de mantener la infección en una fase asintomática prolongada, que normalmente dura varios años y que culmina en la presencia de un incremento en la viremia con una consecuente disminución en el conteo de linfocitos T CD4+, que confiere inmunosupresión. Cuando el conteo de linfocitos T CD4+ desciende por debajo de 200 cel/mm3, o aparecen enfermedades oportunistas o definitorias, se define que la persona presenta enfermedad avanzada por VIH. Objetivo: Determinar el porcentaje de adherencia terapéutica, en los pacientes con VIH del HGZ/MF N°12. Material y Métodos: se realizó un estudio descriptivo, prospectivo, transversal, observacional, cuantitativo; en pacientes con VIH del HGZ/MF N°12 con la obtención de la información a través del instrumento de recolección Morisky-Green modificado que permitió conocer el porcentaje de adherencia al tratamiento. Se utilizo estadística descriptiva, asociación de variables utilizando la Chi cuadrada. Registro de SIRELCIS R-2022-1603-004. Resultados: Se estudio un total de 50 pacientes ambos sexos de ellos 14 (28%) fueron mujeres y 36 (72%) hombres, la edad promedio en años fue de 41-60 años, se observa 46 pacientes (82%) tienen una adecuada adherencia terapéutica. Conclusión: el 92% de los pacientes con diagnóstico de VIH del HGZ/MFNo.12 tienen una adecuada adherencia terapéutica.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18718; info:eu-repo/classification/cti/3; FCMB-E-2024-0066; VIH; Porcentaje; Adherencia terapéutica